The Role of The Community in Winning the Elections - Ahmad Amiruddin (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This study illustrates the role of the community winning candidates in local electionswhere the community is involved in winning politics. This paper explains and analyzesthe role of the community which tends to have an influence in influencing voterscompared to political parties at the community level. The role of the communitybecomes an alternative for the community both in the city and in the village in buildingsocial relations. Based on the desire to maintain harmony among society. In the contextof democratic society is the sole holder of the highest sovereignty, so it cannot be deniedthat in social strata sometimes formed social groups such as communities, associationsthat can determine how the journey of democratic life. For the political community isa necessity that must be faced to achieve goals and defend their interests, thedevelopment of the community in South Sulawesi is quite high, which is formed fromevery level of society, even the general public and youth communities have animportant role in the implementation of elections.